Potencjał informacyjny Bibliografii Historii Śląska = Informational potential of the Bibliography of the Historyof Silesia - Gębołyś, Zdzisław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The tradition of creating a historical bibliography in Silesia, covering the entire territory of this region, dates back to the 19th century. In the twentieth century, these activities intensified. They were led by three main nations: Polish, German and Czech. They ran along this track almost until the end of the 20th century. However,it was only at the end of this millennium that national efforts were combined and a joint scientific and publishing initiative was established, registering Silesian historical writings. The article, after a short historical introduction, presenting the beginnings and development of Silesian historical bibliographies, describes the resources of the Bibliography, including the printed part and the bibliographic database. The main attention was paid to the assessment of the efficiency and informationvalue of the Bibliography of Silesian History as those factors that determine accessto the Bibliography and its use in scientific work. In terms of information efficiency, attention was paid to the layout of the bibliography; indexes; search methods;bibliographic description and editorial structure. The information value was assessed through the formal and content criteria used in the Bibliography. The conclusions drawn from the analysis make the Bibliography positively assessed from both points of view. At the same time, some short comings were indicated which, although they do not lower the value and information efficiency, will weaken it to some extent. We mean, in particular, the subject index, which is flawed from the point of view of the bibliographic methodology, and the criteria for the selection of bibliographic material are not precisely specified.
Keywords: "Bibliografia Historii Śląska"; 1976-2015; sprawność informacyjna; wartość informacyjna; zasoby; "Bibliography of the History of Silesia"; information efficiency; informative value; resources